Identification of endophytic fungi of grapevine with emphasis on the causal agents of grapevine trunk disease in the vineyards of Zanjan Province in Iran. Issue 1 (15th December 2022) - Ghasemi Esfahlan, Saeid; Hemmati, Roghayeh; Mohebbi, Shohreh; Batley, Jacqueline; Arzanlou, Mahdi
Abstract: Trunk disease is a major problem on grapevine in Zanjan province, causing serious decline, despite which its aetiology remains unknown. The purpose of this study was to investigate factors involved in grapevine decline in vineyards of Zanjan province. Samples were collected from twigs and branches of grapevines in the region between October and November 2018. Fungal isolates were identified based on morphological characteristics and ITS‐rDNA sequence data for selected isolates. The frequency and diversity of the fungal community recovered from grapevines in Darreh Sejin in Zanjan province were higher than in other regions. A total of 112 fungal isolates comprising 22 species were recovered. Phaeoacremonium minimum, Microsphaeropsis olivacea and Kalmusia variispora were identified as the dominant species in the region examined and could be considered the main trunk pathogens of grapevines in Zanjan region. In inoculation tests, M. olivacea was proved to be pathogenic on grapevine for the first time in this study.